1953
DOI: 10.1002/jsfa.2740040601
|View full text |Cite
|
Sign up to set email alerts
|

The water‐soluble carbohydrates of grasses. II. —Grasses cut at grazing height several times during the growing season

Abstract: Four perennial grasses were cut with a motor mower each time they reached a height of about 8-10 in. during the growing seasons of 1951 and 1952. The water-soluble carbohydrates, glucose and fructose (reported together as free hexoses), sucrose and fructosan were determined in each cut. Grasses in which the growing point had recently changed to a floral development (in May or June) contained more carbohydrate than grass grown and cut later in the season. The primary reason for this was that the later grasses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1955
1955
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Cocksfoot tends to have a lower non-protein nitrogen content than ryegrass (Table 10) and also has a lower content of soluble sugar than other species (Waite & Boyd, 19536). These observations are both in accordance with the view that cocksfoot is particularly efficient in rapidly synthesizing structural material, and may account in part for the rapidity of growth which it normally displays.…”
Section: Production From Fertilizer Nitrogensupporting
confidence: 69%
See 1 more Smart Citation
“…Cocksfoot tends to have a lower non-protein nitrogen content than ryegrass (Table 10) and also has a lower content of soluble sugar than other species (Waite & Boyd, 19536). These observations are both in accordance with the view that cocksfoot is particularly efficient in rapidly synthesizing structural material, and may account in part for the rapidity of growth which it normally displays.…”
Section: Production From Fertilizer Nitrogensupporting
confidence: 69%
“…These results suggest that there may be wider differences between species than is generally thought. More detailed evidence of some of these differences is given by Waite & Boyd (19536). The botanical composition of the swards Botanical analyses were carried out by a simplified Point Quadrat method at the end of each season, at least ten sampling frames each of ten each grass and treatment, being means of three replicates for all except treatment 2X, 2Y and 2Z, are too bulky for presentation but are available on application to the authors.…”
Section: Non-protein Nitrogen Crude Fibre and Ether Extractmentioning
confidence: 99%
“…Although dietary intake is dependent on the feed provided, it is also influenced in grazing animals by seasonal fluctuations in the relative composition of herbage. Waite and Boyd (1953) demonstrated that the nonstructural carbohydrate content of grasses was greatest in late spring, declined in mid summer and then reached medium levels in early autumn. Similarly, fluctuations in grass protein content also show a seasonal pattern, being highest when the plant is young (spring) and declining at the time of ear emergence (summer) (Green et al .…”
Section: Introductionmentioning
confidence: 99%
“…Grasses native to temperate latitudes, such as timothy and orchardgrass, accunmulate sucrose and fructosan ( 1,4,7,12,13). Extraction of total available carbohydrates has been accomplished by acid hydrolysis (8) or with water (1,14,15) since fructosan is soluble in water. Starch, however, is largely water-insoluble.…”
mentioning
confidence: 99%